In vitro anti-estrogenic potential of FertiZen-R™- a nutraceutical ingredient for estrogen modulation - Gadani, Mihir; Upadhyay, Ratna; Raut, Supriya; Badak, Sneha (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2023)
Background: According to CDC, polycystic ovarian syndrome (PCOS) is responsible for infertility in women with 6-12% incidences all over the world. The current treatment options available have several side effects such as amenorrhea and obesity amongst others. Dietary interventions such as non-estrogenic and androgen-suppressing foods along with nutraceutical products is considered for treating PCOS with minimum side effects. One such product of Zenherbs lab called FertiZen-R™ is a combination of three phytochemicals from three plants viz., Foeniculum vulgare, Linum Usitatissimum, Glycyrrhiza glabra, hibiscus extract and is developed as a product to treat and control PCOS. Methods: The FertiZen-R™ was quantified for the presence of phytochemicals such as glycyrrhizic acid, polyphenols, and saponins. It was further tested for estrogenic/anti-estrogenic potential on estrogen-positive breast cancer cell line (MCF-7) using an E-Screen assay. Results: The FertiZen-R™ showed presence of 5% glycyrrhizinic acid, 5% saponins, and 2-3% polyphenols. It exhibited a strong anti-estrogenic potential with 40-50% inhibition from concentrations as low as 0.156 mg/ml like tamoxifen (IC50 at 0.156 mg/ml), while inositol, a natural growth promoter, showed no effect on the cell viability. Conclusions: FertiZen-R™ showed anti-estrogenic potential when tested in-vitro and can be used to treat PCOS in women even with ER-positive breast cancer cells. However, clinical studies to determine the dosage are required to warrant the potential of FertiZen-R™.